Paleomagnetism and K-Ar Dating of Some Franklin Lavas and Diabases, Victoria Island - Palmer, H. C.; Hayatsu, A. (Canadian Journal of Earth Sciences, 1975)
Lavas of the Natkusiak Formation and related diabase sills, Victoria Island, have single polarity remanence directions, which yield a paleomagnetic pole at 163°E, 07°S, which is similar to that obtained from the Coronation Sills of the adjacent mainland. These western Arctic poles are slightly, but significantly different from those obtained from Franklin sills and dikes exposed in the central and eastern Arctic. K–Ar data indicate no resolvable difference in age between the western and eastern Arctic rocks. Although the apparent K–Ar ages from the Victoria Island lavas and sills are discordant, the highest apparent ages are in agreement with a K–Ar isochron age of 625 m.y. obtained from samples of the least altered lavas.